Cuba a 20 años de El Cairo - Dixie Edith Trinquete Díaz (Universidad de La Habana, 2014)
Resumen Se realiza una reseña sobre el panel del Proceso de seguimiento del cumplimiento del Programa de Acción de El Cairo (Cairo + 20) realizado en el Centro de Estudios Demográficos con la participación de representantes del MINREX, MINCEX, ONEI, CENESEX y UNFPA como panelistas. Participaron además representantes de otras organizaciones e instituciones nacionales. Abstract This is a review about the panel of the Process of pursuit of the execution of the Program of Action of Cairo (Cairo + 20) carried out in the Center of Demographic Studies with the participation as panelists of representatives of MINREX, MINCEX, ONEI, CENESEX and UNFPA. Representatives of other organizations and national institutions also participated.